Hubungan Antara Tingkat Stres dengan Kejadian Sindrom Pra Menstruasi Pada Siswi SMP - Natasya, Bella; Handayani, Ririn; Fitrianingtyas, Rizki; Maryanti, Syiska Atik (Jurnal Kebidanan Malakbi, 2026)
Premenstrual Syndrome (PMS) among adolescents significantly impacts productivity and mental health. In Indonesia, the prevalence of PMS continues to rise, with approximately 80% of adolescent girls experiencing symptoms severe enough to disrupt daily activities. Among junior high school students, PMS often leads to decreased concentration, impaired social communication, and increased absenteeism. This study aimed to analyze the relationship between stress levels and the incidence of PMS in junior high school students in Arjasa. Using a quantitative correlation method with a cross-sectional design, data were collected from 158 adolescent girls at SMPN 1 Arjasa. A sample of 61 respondents was selected via simple random sampling. Instruments used included the DASS-21 (Depression Anxiety Stress Scale) and the sPAF (Shortened Premenstrual Assessment Form) questionnaires. Statistical analysis using the Chi-Square test yielded a p-value of 0.031 (α < 0.05), indicating a significant relationship between stress levels and the incidence of PMS. These findings suggest that stress is a significant predictor of PMS. Consequently, students are encouraged to implement independent stress management techniques, such as scheduling relaxation, ensuring adequate rest, and engaging in regular physical exercise.